Strong-motion characteristics of two 2022 M 6.5 + disastrous earthquakes in the southern longitudinal valley, Taiwan - Lin, Yen-Yu; Wen, Yi-Ying; Chen, Chun-Te; Yen, Yin-Tung (Earth, planets, and space, 2025)
Two disastrous earthquakes, the M L 6.6 Guanshan and M L 6.8 Chihshang earthquakes, called the 0917 and 0918 events, respectively, occurred in the southern longitudinal valley (LV) of eastern Taiwan within a 17-h interval in 2022. In the present study, we document the observed strong ground motions and damage distributions and analyze the source properties of both events via broadband (0.2 ~ 10 Hz), near-field, strong-motion seismic records. The results of Empirical Green’s function (EGF) analysis reveal that the 0917 event ruptured to the south in a single strong-motion generation area (SMGA), with a size of 47.04 km 2 , and that the 0918 event ruptured to the north through two SMGAs, with a combined size of 80.16 km 2 . The SMGA models explain the observed velocity pulses that caused severe damage well. Using the source-scanning algorithm technique, we obtain the centroid locations of both events on the west-dipping Central Range Fault (CNF), indicating that the 0917 and 0918 events had southward directivity and northward directivity, respectively, which are consistent with the results from the EGF method. We summarize that the velocity pulses of both events could be attributed to rupture directivity, high stress drops, and shallow ruptures from the obtained SMGA(s). Combined with the findings of previous studies of moderate-to-large earthquakes occurring in the LV, seismic hazard assessment and mitigation are important because of the interaction between the west-dipping CNF and the east-dipping LV fault, especially for the shallow part above a depth of 10 km. Graphical Abstract